2009
DOI: 10.2217/pgs.09.102
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in Side Effects of Psychotropic Drugs: Genes or Gender?

Abstract: Sex differences observed in the adverse effects associated with psychotropic drugs have not been reported consistently in the literature. In this review, we discuss the current published data on sex differences observed in the occurrence, symptomatology and reporting of the adverse effects associated with psychotropic drug effects, and discuss their clinical relevance. We reviewed the published data up to April 2009 on sex differences in the side effects of antipsychotics, antidepressant and mood stabilizers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 181 publications
(190 reference statements)
4
44
0
2
Order By: Relevance
“…One reason for this being that clozapine, an antipsychotic that also causes considerable weight gain in humans, does not appear to do so in rats (Cooper et al 2008). There is considerable evidence however to suggest that females are more liable to incur antipsychotic-induced weight gain (Aichhorn et al 2007;Haack et al 2009;Hakko et al 2006), although this may reflect gender differences in drug pharmacokinetics (Beierle et al 1999;Harris et al 1995). In the present study, we observed a number of gender differences in baseline levels of the plasma cytokines IL-1β and IL-6 as well as local levels of IL-6 in the adipose tissue which may impact on susceptibility to the effects of AAPDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for this being that clozapine, an antipsychotic that also causes considerable weight gain in humans, does not appear to do so in rats (Cooper et al 2008). There is considerable evidence however to suggest that females are more liable to incur antipsychotic-induced weight gain (Aichhorn et al 2007;Haack et al 2009;Hakko et al 2006), although this may reflect gender differences in drug pharmacokinetics (Beierle et al 1999;Harris et al 1995). In the present study, we observed a number of gender differences in baseline levels of the plasma cytokines IL-1β and IL-6 as well as local levels of IL-6 in the adipose tissue which may impact on susceptibility to the effects of AAPDs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors, such as baseline weight (Basson et al 2001;Gebhardt et al 2009), therapeutic outcome (Basson et al 2001;Meltzer et al 2003) and gender (Aichhorn et al 2007;Haack et al 2009), have been proposed to confer susceptibility to the metabolic effects of antipsychotics. In the majority of cases, females have been found to have a higher prevalence of AAPD-induced weight gain (Aichhorn et al 2007;Haack et al 2009;Hakko et al 2006;Verma et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 A gender difference in D2-like receptors could be related to gender differences in the antipsychotic drug response such as tardive dyskinesia which seems to be more frequent in female gender 79 such as the increase in body weight. 80 However, men have markedly greater dopamine release than women in the striatum and men's ratings of the positive effects of amphetamine are larger than women's. This could be responsible for increased vulnerability to stimulants and methamphetamine toxicity.…”
Section: Analgesic and Neuropsychiatric Drugsmentioning
confidence: 99%
“…Drug-induced weight gain and metabolic syndrome induced by antipsychotic drugs, symptoms of sexual dysfunction caused by antidepressants and antipsychotic, and cardiac arrhythmic are sex/gender specifi c. Notably, women might differ from men not only in incidence but also in the presentation of clinical symptoms associated with adverse psychotropic drug effects. 80 Local anesthetic: procainamide such as quinidine, hydralazine, and methyldopa are casually associated with drug-induced lupus. 86 This resolves completely within weeks or months after withdrawal of the causative agent, and although the female preponderance is not as marked in drug-induced lupus as in idiopathic lupus, female sex has been identifi ed as a risk factor for developing drug-induced lupus.…”
Section: Analgesic and Neuropsychiatric Drugsmentioning
confidence: 99%